Kolostori kutatómunka Mongóliában - Majer, Zsuzsa (Távol-keleti Tanulmányok, 2018)
The article describes the author’s fieldworks and research on different topics in Mongolian Buddhist monasteries between 1999 and 2017. The research topics included the history and revival of Mongolian monasteries, description of different Mongolian Buddhist moansteries the ceremonial life and ceremonial system in Mongolian temples, description of different special Mongolian Buddhist ceremonies, and currently the Tibetan language afterdeath rites in Mongolian Buddhist practice. The fieldworks are described in chronological order, and the emphasis is laid on describing the circumstances of the investigations, as well as the difficulties the researchers had to face. All researches are described briefly, with references to the publications where research outcomes are published.